Clinical and laboratory characteristics in juvenile-onset systemic lupus erythematosus across age groups. (April 2020) - Massias, J S; Smith, E M D; Al-Abadi, E; Armon, K; Bailey, K; Ciurtin, C; Davidson, J; Gardner-Medwin, J; Haslam, K; Hawley, D P; Leahy, A; Leone, V; et al.
Background: Systemic lupus erythematous (SLE) is a systemic autoimmune/inflammatory condition. Approximately 15–20% of patients develop symptoms before their 18th birthday and are diagnosed with juvenile-onset SLE (JSLE). Gender distribution, clinical presentation, disease courses and outcomes vary significantly between JSLE patients and individuals with adult-onset SLE. This study aimed to identify age-specific clinical and/or serological patterns in JSLE patients enrolled to the UK JSLE Cohort Study. Methods: Patient records were accessed and grouped based on age at disease-onset: pre-pubertal (≤7 years), peri-pubertal (8–13 years) and adolescent (14–18 years). The presence of American College of Rheumatology (ACR) classification criteria, laboratory results, disease activity [British Isles Lupus Assessment Group (BILAG) and Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2 K) scores] and damage [Systemic Lupus International Collaborating Clinics (SLICC) damage index] were evaluated at diagnosis and last follow up. Results: A total of 418 JSLE patients were included in this study: 43 (10.3%) with pre-pubertal disease onset; 240 (57.4%) with peri-pubertal onset and 135 (32.3%) were diagnosed during adolescence. At diagnosis, adolescent JSLE patients presented with a higher number of ACR criteria when compared with pre-pubertal and peri-pubertal patients [pBILAG2004 scores: 9(4–20] vs. 7(3–13] vs. 7(3–14], respectively, p  = 0.015] with increased activity in the following BILAG domains: mucocutaneous ( p  = 0.025), musculoskeletal ( p  = 0.029), renal ( p  = 0.027) and cardiorespiratory ( p  = 0.001). Furthermore, adolescent JSLE patients were more frequently ANA-positive ( p  = 0.034) and exhibited higher anti-dsDNA titres ( p  = 0.001). Pre-pubertal individuals less frequently presented with leukopenia ( p  = 0.002), thrombocytopenia ( p  = 0.004) or low complement ( p  = 0.002) when compared with other age groups. No differences were identified in disease activity (pBILAG2004 score), damage (SLICC damage index) and the number of ACR criteria fulfilled at last follow up. Conclusions: Disease presentations and laboratory findings vary significantly between age groups within a national cohort of JSLE patients. Patients diagnosed during adolescence exhibit greater disease activity and "classic" autoantibody, immune cell and complement patterns when compared with younger patients. This supports the hypothesis that pathomechanisms may vary between patient age groups.